Protective effects and molecular mechanisms of tea polyphenols on cardiovascular diseases - Guo, Jun; Li, Kai; Lin, Yajun; Liu, Yinghua (Frontiers in Nutrition, 2023)
Aging is the most important factor contributing to cardiovascular diseases (CVDs), and the incidence and severity of cardiovascular events tend to increase with age. Currently, CVD is the leading cause of death in the global population. In-depth analysis of the mechanisms and interventions of cardiovascular aging and related diseases is an important basis for achieving healthy aging. Tea polyphenols (TPs) are the general term for the polyhydroxy compounds contained in tea leaves, whose main components are catechins, flavonoids, flavonols, anthocyanins, phenolic acids, condensed phenolic acids and polymeric phenols. Among them, catechins are the main components of TPs. In this article, we provide a detailed review of the classification and composition of teas, as well as an overview of the causes of aging-related CVDs. Then, we focus on ten aspects of the effects of TPs, including anti-hypertension, lipid-lowering effects, anti-oxidation, anti-inflammation, anti-proliferation, anti-angiogenesis, anti-atherosclerosis, recovery of endothelial function, anti-thrombosis, myocardial protective effect, to improve CVDs and the detailed molecular mechanisms.